CodY Is a Nutritional Repressor of Flagellar Gene Expression in Bacillus subtilis - Bergara, F. (American Society for Microbiology, 2003)
Expression of the σ(D)-dependent flagellin gene, hag, is repressed by the CodY protein in nutrient-rich environments. Analysis of a codY mutant bearing a hag-lacZ reporter suggests that the availability of amino acids in the environment is the specific signal that triggers this repression. Further, hag-lacZ expression appears to be sensitive to intracellular GTP levels, as demonstrated by increased expression upon addition of decoyinine. This result is consistent with the postulate that the availability of amino acids in the environment effects intracellular GTP levels through the stringent response. However, the levels of hag-lacZ measured upon the addition of subsets of amino acids suggest an additional mechanism(s). CodY is a DNA binding protein that could repress flagellin expression directly by binding to the hag promoter region, or indirectly by binding to the fla/che promoter region that governs expression of the σ(D) transcriptional activator required for hag gene expression. Using an electrophoretic mobility shift assay, we have demonstrated that purified CodY protein binds specifically to both the hag and fla/che promoter fragments. Additionally, CodY acts as a nutritional repressor of transcription from the fla/che promoter region that contains two functional promoters. CodY binds to both the σ(D)- and σ(A)-dependent promoters in this region, as demonstrated by DNase I footprint analyses. Footprint analyses of the hag gene demonstrated that CodY binds downstream of its σ(D)-dependent promoter. Taken together, these results identify new members of the CodY regulon that encode motility functions in Bacillus subtilis and are controlled by the σ(D) alternate sigma factor.